Polyimide-Based Dielectric Materials for High-Temperature Capacitive Energy Storage - Lingling Liu; Li Li; Shixian Zhang; Wenhan Xu; Qing Wang (Electronic Materials)
Polyimide (PI) has received great attention for high-temperature capacitive energy storage materials due to its remarkable thermal stability, relatively high breakdown strength, strong mechanical properties, and ease of synthesis and modification. In this review, several key parameters for evaluating capacitive energy storage performance are introduced. Subsequently, the properties of the commercially available PIs are presented. Then, the recent development of designing and tailoring all-organic PI-based polymers is discussed in detail, focusing on molecular composition and spatial configuration to enhance dielectric constant, breakdown strength, discharged energy density, and charge-discharge efficiency. Finally, we outline the current challenges and future development directions of PI-based high-temperature energy storage dielectric materials.